2013
DOI: 10.1111/all.12127
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled nitric oxide in symptomatic children at preschool age predicts later asthma

Abstract: In this cohort of high-risk preschool children, elevated FeNO is associated with increased risk for school-age asthma. The new API including FeNO identifies children at risk of later asthma comparably to the classical API, but does not require blood sampling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
84
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 36 publications
3
84
0
4
Order By: Relevance
“…This study differs from earlier studies on the predictive value of FeNO for asthma later in life as it included children from general paediatric practices before the first episode of wheezing and measured FeNO with an online single breath technique. The results were in line with earlier studies suggesting an association between FeNO early in life and respiratory symptoms, lung function, airways reactivity and/or asthma later in life [7][8][9][10][11]. The different populations studied, the different techniques used to measure FeNO and the different outcomes assessed may explain conflicting results with other studies [12][13][14].…”
supporting
confidence: 87%
See 2 more Smart Citations
“…This study differs from earlier studies on the predictive value of FeNO for asthma later in life as it included children from general paediatric practices before the first episode of wheezing and measured FeNO with an online single breath technique. The results were in line with earlier studies suggesting an association between FeNO early in life and respiratory symptoms, lung function, airways reactivity and/or asthma later in life [7][8][9][10][11]. The different populations studied, the different techniques used to measure FeNO and the different outcomes assessed may explain conflicting results with other studies [12][13][14].…”
supporting
confidence: 87%
“…Although in the study by SINGER et al [7] the positive predictive value of the modified index could not be increased by FeNO, ELLIOTT et al [9] recently showed that FeNO in children with a mean age of ∼15 months with recurrent wheezing episodes had high positive and negative predictive values for wheezing and acute exacerbations at age 3 years, and also for a decline in lung function between 15 months and 3 years.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Taken together, while there is cumulative evidence that elevated FeNO in high-risk children after a possible impact by environmental exposures is associated with later asthma [4,5], it is unknown if FeNO after birth, prior to a possible influence by post-natal environmental exposures and first respiratory symptoms, is associated with asthma. Given that environmental factors are known to induce NOS activity and modify FeNO [6,7,11,12], we hypothesised that FeNO measured after birth, and before relevant exposure to these factors, is not associated with asthma at school age.…”
mentioning
confidence: 99%
“…The interpretation of FeNO, its predictive value and its modifiers are age dependent [4,5,7,[9][10][11]. Postnatal FeNO metabolism seems to be modified by various environmental factors.…”
mentioning
confidence: 99%